Formulation of Bacillus and Azotobacter Consortia in Liquid Cultures: Preliminary Research on Microbes-Coated Urea - Reginawanti Hindersah; Mieke Rochimi Setiawati; Priyanka Asmiran; Betty Natalie Fitriatin (Hasanuddin University, 2020)
The spore-forming Bacillus and cysts forming Azotobacter are Plant Growth Promoting Rhizobacteria which has been used as biofertilizer in sustainable agriculture since they tolerant to dried soil. Drought resistant microbes will be useful to coat urea in order to reduce the lost of nitrogen. The objectives of this preliminary study were to study the effect of molasse based liquid media on the population of Bacillus spore and Azotobacter vegetative cell and to determine the composition of four bacterial species in liquid formula. In the first experiment The Bacillus subtilis, B. megaterium, A. chroococcum and A. vinelandii were grown separately in 1% cane molasses enriched with 0.1% NH4Cl. As control treatment, The Bacillus and Azotobacter were grown in Nutrient Broth and Ashby’s mannitol broth respectively. In the second experiment, different composition of said Bacillus and Azotobacter were grown in molasses based liquid media prior to count the spore and vegetative cell. The results showed that molasses-based media supported bacterial growth and initial ratio 1:1:1:1 of liquid inoculant was effective to increase bacterial growth. This experiment suggested that the use of organic based media was useful practice of liquid biofertilizer formulation for granule urea coating.